THE EFFECTIVITY OF BIOFEEDBACK ON REESTABLISHING POSTURAL SYMMETRY IN HEMIPLEGIC PATIENTS - Güldal Funda Nakipoğlu; Ayşe Karamercan; Aynur Karagöz; Neşe Özgirgin (Archives of Rheumatology, 2002)
In the rehabilitation of hemiplegic patients resulting from cerebrovasculer accident (CVA); two of the most commonly faced problems are not being able to control the posture and bearing of weight symmetrically. In this study, we planned to investigate the efficacy of biofeedback in the improvement of symmetric weight bearing and posture control in hemiplegic patients. Sixty patients were grouped into two randomly. Thirty patients participated the program of rehabilitation by the biofeedback and conventional methods and the other thirty patients had conventional weight bearing and postural control therapy. Sitting balance, sitting to standing, walking scales of Modified Motor Assesment Scale (MMAS) and Trunk Control Test (TCT) were applied and percentage of Postural Symmetry (PS) of patients were calculated. The group of patients who received biofeedback and conventional methods showed a statistically significant decrease in the percentage of PS, and an increase in the scores of MMAS and TCT when compared with the group of patient who received conventional methods only. According to the results of our study; we suggest that in the regaining of postural control and symmetric weight bearing in hemiplegic patients resulting from CVA, conventional methods with biofeedback treatment establish more effectiveness than conventional methods only.